2016
DOI: 10.1044/2015_ajslp-14-0113
|View full text |Cite
|
Sign up to set email alerts
|

Be Clear: A New Intensive Speech Treatment for Adults With Nonprogressive Dysarthria

Abstract: The results of this study suggest that this new intensive treatment may have potential as an effective intervention for nonprogressive dysarthria. However, controlled studies are required to establish treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 45 publications
3
58
0
Order By: Relevance
“…Targeting speech clarity has shown promise for increasing intelligibility in adults with dysarthria (e.g., Park et al . 2016). In cueing studies, when native speakers of American English increase movement amplitude in clear speech, the first formant (F1) range generally increases across vowels.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting speech clarity has shown promise for increasing intelligibility in adults with dysarthria (e.g., Park et al . 2016). In cueing studies, when native speakers of American English increase movement amplitude in clear speech, the first formant (F1) range generally increases across vowels.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the underlying acoustic changes that accompany clear speech variants in speakers with PD is important for optimizing clear speech training programs (e.g., Park, Theodoros, Finch, & Cardell, 2014). Furthermore, improved understanding of the acoustic basis of dysarthria can inform therapy decisions (Duffy, 2013) as well as provide insight into a model of dysarthria (Duffy, 2005;Kain, Amano-Kusumoto, & Hosom, 2008;Mengistu & Rudzicz, 2011).…”
mentioning
confidence: 99%
“…Tjaden et al (2014) observed that producing both clear and loud speech resulted in increased speech intelligibility relative to slow and habitual speech for speakers with multiple sclerosis or PD. Increased speech intelligibility has also been observed posttreatment following an intensive therapy using clear speech in speakers with nonprogressive dysarthria (Park, Theodoros, Finch, & Cardell, 2016).…”
Section: Global Strategiesmentioning
confidence: 93%